Capital structure decisions, agency conflicts and corporate performance: Evidence from Sri Lankan listed manufacturing firms - Vijayakumaran, R. (International Journal of Accounting & Business Finance, 2015)
Corporate capital structure decisions are key determinants of firm performance. The agency theory suggeststhat debt financing is one of the mechanismsto mitigate agency problems and thusto improve firm performance. This paper provides important evidence on the performance effects of capital structure decisions using a panel of listed manufacturing firms in the Colombo Stock Exchange (CSE) over the period 2008-2013. The Generalized Method of Moments (GMM) methodology is used to control for unobserved heterogeneity, endogeneity of capital structure decisions, and their dynamics. The study documentsthat leverage is non-linearly (U-shaped)related to firm performance.
Keywords: Capital structure decisions; agency problem; coporate governance; corporate performance